Evaluating the Tobii pro fusion-120Hz eye tracker for clinical use - Mohamed Nazim, Anis Najihah; Che Arif, Fatin Amalina; Zahari, Ilyanoon; Shafee, Noor Wafirah (IIUM Press, 2024)
Background: This study aims to evaluate the performance of the Tobii Pro Fusion-120Hz in producing normative data for saccadic peak velocity, with the results compared to the higher sampling rate EyeLink 1000 Plus, which has already been validated for clinical use. Methods: Thirty participants (aged 20-23) with normal ocular motility and best-corrected visual acuity of 0.2 log MAR or better were recruited. Exclusion criteria included high myopia, ocular trauma, brain injuries, and the use of rigid gas-permeable contact lenses. Saccadic movements were measured using the Tobii Pro Fusion 120Hz eye tracker. Data were recorded and analysed using Tobii Pro Lab Software and SPSS version 23. Calibration accuracy and precision thresholds were set at 0.5° and 0.2°, respectively. Participants completed 24 saccadic trials tested binocularly, and the recorded peak velocity data was compared with data validated using the higher sampling rate devices (500Hz). Results: The one-sample t-test showed no significant difference in saccadic peak velocity (p = 0.40) between the lower sampling rate and the higher sampling rate, indicating that the former can produce saccadic peak velocity measures comparable to those of the latter. Conclusion: Normative data for saccadic peak velocity were provided in this study using the Tobii Pro Fusion-120Hz, confirming its accuracy for clinical assessments and its potential for clinical application.